Effect of strain path on microstructure and texture formation in cold-rolled and annealed FCC equiatomic CoCrFeMnNi high entropy alloy. (August 2017) - Reddy, S.R.; Ahmed, M.Z.; Sathiaraj, G.D.; Bhattacharjee, P.P.
Abstract: The effect of strain path on microstructure and texture formation in an equiatomic CoCrFeMnNi high entropy alloy was investigated. For this purpose, the alloy was cold-rolled to 90% reduction in thickness (total equivalent strain ( ε e q ) ∼ 2.65 ) using unidirectional cold-rolling (UCR) and different cross-rolling routes. In the MSCCR route, the samples were rotated by 90° around the ND in between each pass. In the TSCCR(90°) and TSCCR(45°) routes, the samples were deformed by unidirectional rolling to half of the ε e q (∼1.3) in the first step and the rest half of the strain ( ε e q ∼1.3) was imparted after rotation around the ND by 90° and 45°, respectively. The development of deformation microstructures in all the processing routes were characterized by fine lamellar type structure intercepted by inclined shear bands. The TSCCR(45°) processed material appeared to be most prone to shear band formation. The UCR processed material showed brass type texture, while the textures of different cross-rolled materials were featured by different rotated brass components. Upon annealing, the UCR processed material showed the lowest grain size while the highest grain size was observed in the TSCCR(45°) processed material. This indicated greater available nucleation sites in the UCR processed material as compared to the TSCCR(45°) processed material. The differences in annealed grain size was presumably higher due to substructure destabilization and misorientation build-up diminishing the number of potential nuclei in the TSCCR(45°) processed material. The annealing textures of the differently processed materials were featured by the presence of α-fiber (ND//<110>) and absence of preferential nucleation and growth. Highlights: Effect of strain path on microstructure and texture is reported. Cross-rolling affects shear band density and deformation texture. Annealed grain sizes are higher in cross-rolled materials. Annealing textures remain affected by preferential nucleation or growth. The TSCCR(45°) route shows the most profound effects.